DIAGNOSTIC VALUE OF SERUM UREA, CREATININE, SODIUM AND POTASSIUM FOR COMPLICATED APPENDICITIS - A ONE YEAR RETROSPECTIVE STUDY - Maqbool, Mishal; Khaliq, Fatima; Mehboob, Amina; Anis, Salwa; Hussain, Maqbool; Amjad, Muhammad (Journal of Ayub Medical College Abbottabad, 2022)
Background: Acute appendicitis is a common surgical emergency and if complicated, manifesting as abscess, perforation, suppurative or gangrenous appendicitis, carries significant morbidity and mortality. Its early preoperative diagnosis can improve outcome in patients and reduce incidence of negative appendectomies. It, however, mandates identification of new diagnostic parameters for it. This retrospective study evaluates diagnostic accuracy of serum urea, creatinine, sodium and potassium for complicated appendicitis. Methods: 60 patients with suspected appendicitis were grouped into complicated and uncomplicated appendicitis based on histological reports. Preoperative laboratory results for serum urea, creatinine, sodium and potassium levels were obtained from hospital records. Diagnostic strength of these markers was calculated as specificity, sensitivity and area under curve. ROC curve analysis was used for their diagnostic accuracy. Results: The levels of serum urea, creatinine and K were not significantly different in uncomplicated and complicated appendicitis. However, sodium was significantly higher in complicated appendicitis. ROC curve analysis showed AUC values for all the studied variables to be greater than 0.5. However, none of the markers had good capability to differentiate complicated appendicitis from uncomplicated appendicitis. Conclusion: Serum urea, creatinine, sodium and potassium levels have shown a tendency to be predictive of complicated appendicitis but a strong association could not have been established. Hence, further investigation is warranted